Commitment Point during G(0)→G(1) That Controls Entry into the Cell Cycle - Lea, Nicholas C. (American Society for Microbiology, 2003)
Initiation of T-lymphocyte-mediated immune responses involves two cellular processes: entry into the cell cycle (G(0)→G(1)) for clonal proliferation and coordinated changes in surface and secreted molecules that mediate effector functions. However, a point during G(0)→G(1) beyond which T cells are committed to enter the cell cycle has not been defined. We define here a G(0)→G(1) commitment point that occurs 3 to 5 h after CD3 and CD28 stimulation of human CD4 or CD8 T cells. Transition through this point requires cdk6/4-cyclin D, since inhibition with TAT-p16(INK4A) during the first 3 to 5 h prevents cell cycle entry and maintains both naive and memory T cells in G(0). Transition through the G(0)→G(1) commitment point is also necessary for T cells to increase in size, i.e., to enter the cellular growth cycle. However, transition through this point is not required for the induction of effector functions. These can be initiated while cells are maintained in G(0) with TAT-p16(INK4A). We have termed this quiescent, activated state G(0(A)). Our data provide proof of the principle that entry of T cells into the cell cycle and cellular growth cycles are coupled at the G(0)→G(1) commitment point but that these processes can be uncoupled from the early expression of molecules of effector functions.